PENTINGNYA MEMBERIKAN PEMBELAJARAN MENYENANGKAN KEPADA ANAK USIA DINI - Yulia, Yulia Pratiwi Siregar; Nurlaila; Hasibuan, Masnilam (Universitas Aufa Royhan Di Kota Padangsidipuan, 2025)
Learning in early childhood can be carried out by implementing fun learning, namely by using the play while learning learning model so that learning objectives can be achieved optimally. This community service activity aims to increase knowledge and insight regarding fun learning models that can be used by teachers so that learning objectives can be achieved optimally. The data collection technique in this community service activity uses unstructured interviews. This method is used to see the extent of children's knowledge and the obstacles they face during the learning process. This community service activity shows that fun learning is effective in increasing children's knowledge and that learning is effective in developing creativity and increasing educators' motivation in providing material so that learning objectives can be achieved. Based on the results of these activities, it can be concluded that fun learning can be applied to early childhood so that these learning activities can increase the feeling of comfort for students, especially in early childhood